Metamaterials: A Metamaterial Emitter for Highly Efficient Radiative Cooling (Advanced Optical Materials 8/2015). Issue 8 (August 2015) - Hossain, Md Muntasir; Jia, Baohua; Gu, Min
<x xml:space="preserve">Abstract</x> Anisotropic metamaterial emitters can serve a key role in highly efficient radiative cooling. Described by M. Gu and co‐workers on page 1047, they are designed to selectively radiate within the atmospheric transparency window and minimize absorption of atmospheric radiation outside the window. Using these unique radiative properties, a device realized with these artificial emitters has the ability to cool down 12 °C below the ambient temperature.